Review of the Bucharest conference "War in Ukraine. What does the future of Central and Eastern Europe look like?" - Stepanenko, Anastasiia (Ukrainian Cultural Studies, 2024)
This review reflects on the "War in Ukraine: What Does the Future of Central and Eastern Europe Look Like?" conference held in Bucharest in November 2024.  Key themes included political shifts in Central and Eastern Europe, the resilience of democratic institutions, the effects of sanctions on Russia, energy security in Europe, and the cultural impact on collective memory and displaced communities. The conference facilitated robust academic discourse and fostered international connections, highlighting the growing interest in Ukrainian studies.